2010
DOI: 10.1016/j.brat.2010.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Constructing a self: The role of self-structure and self-certainty in social anxiety

Abstract: Current cognitive models stress the importance of negative self-perceptions in maintaining social anxiety, but focus predominantly on content rather than structure. Two studies examine the role of self-structure (self-organisation, self-complexity, and self-concept clarity) in social anxiety. In study one, self-organisation and self-concept clarity were correlated with social anxiety, and a step-wise multiple regression showed that after controlling for depression and self-esteem, which explained 35% of the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 48 publications
3
51
0
1
Order By: Relevance
“…One recent study that screened for depression found a mean of 43.49 (Diehl & Hay, 2011), higher than the mean in the HASCI. Given that SCC has been linked to different types of psychopathology including depression and anxiety (Butzer & Kuiper, 2006; van Dijk et al, 2014), social anxiety (Stopa, Brown, Luke, & Hirsch, 2010), and psychopathology being common in the general population (Kessler et al, 2005) the reason there is a significant difference in the original but not the HASCI sample may be due to psychopathology, and resulting lower SCC, in the HASCI sample. Future research could examine whether people with schizophrenia have lower SCC than psychiatric comparison groups such as major depression, generalized anxiety disorder, or bipolar disorder to determine whether low SCC is specific to schizophrenia or related to psychopathology more broadly.…”
Section: Discussionmentioning
confidence: 99%
“…One recent study that screened for depression found a mean of 43.49 (Diehl & Hay, 2011), higher than the mean in the HASCI. Given that SCC has been linked to different types of psychopathology including depression and anxiety (Butzer & Kuiper, 2006; van Dijk et al, 2014), social anxiety (Stopa, Brown, Luke, & Hirsch, 2010), and psychopathology being common in the general population (Kessler et al, 2005) the reason there is a significant difference in the original but not the HASCI sample may be due to psychopathology, and resulting lower SCC, in the HASCI sample. Future research could examine whether people with schizophrenia have lower SCC than psychiatric comparison groups such as major depression, generalized anxiety disorder, or bipolar disorder to determine whether low SCC is specific to schizophrenia or related to psychopathology more broadly.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Wilson and Rapee (2006) concluded that low SCC was a key predictor of social phobia beyond the effect of depressive and anxiety symptoms. Similarly, Stopa et al (2010) also found self-concept clarity to predict social anxiety in a sample of undergraduate studies beyond self-esteem and depression. In short, a disintegrated self-concept could significantly impair individuals' adaptive relationships with others, which further impedes clarifying their self-concept.…”
Section: Diathesis-stress Model Of Compulsive Internet Usementioning
confidence: 83%
“…Building on studies that report a strong link between low self-concept clarity and social anxiety in face-toface contexts (e.g. Stopa, Brown, Luke, & Hirsch, 2010), we expected this trait to be particularly central in predicting a person's likelihood to make up for the difficulties of faceto-face interactions with online encounters. Importantly, we argue that, at low levels of social support and in line with the importance that Davis's (2001) model gives to the social aspects, self-concept clarity would be a key vulnerability factor of CIU.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently been investigating these three different aspects of self-structure, namely, self-complexity, self-concept clarity, and self-organisation (Stopa, Brown, Luke, & Hirsch, 2009). In our first study involving 98 undergraduate students, we found that selfconcept clarity and self-organisation, together with depression and self-esteem, predicted about 40% of the variance in social anxiety scores, but self-concept clarity was the only unique predictor.…”
Section: Self-structure and Social Anxietymentioning
confidence: 99%